Streptococcosis on Nile tilapia (Oreochromis niloticus) in Indonesian freshwater aquaculture - Taukhid, Taukhid; Wajdy, Edy Farid; Sugiani, Desy; Nafiqoh, Nunak (Journal Omni-Akuatika, 2023)
This review aimed to provide the current status of streptococcosis in freshwater aquaculture in Indonesia. So far, this disease has been mostly reported in tilapia aquaculture, and there have been no serious reports of this disease in other species of freshwater aquaculture. The disease is mostly encountered during the dry season or the transition period from the dry season to the rainy season or vice versa. Initially, the disease was mostly reported in tilapia larger than 250 grams, but in its development, it was also reported in smaller fish. The Ministry of Marine Affairs and Fisheries (MMAF) has classified this disease as a major disease in tilapia in Indonesia since 2014. Based on the characteristics of Streptococcus agalactiae isolates collected from diseased tilapia from various regions in Indonesia, two biotypes were found consisting of ?-hemolytic S. agalactiae (biotype I) and non-hemolytic S. agalactiae (biotype II). Biotype I cause disease with acute mortality patterns, while biotype II causes disease with chronic and persistent mortality patterns. Based on susceptibility to S. agalactiae during artificial infection testing, it is known that all tilapia strains that have been released to the public for aquaculture purposes are susceptible to infection with the bacteria; although each strain has a different level of susceptibility. Fish health management strategies that are based on preventive measures and relevant to sustainable aquaculture programs should be based on ecological-biological approaches such as the implementation of biosecurity systems, the use of vaccines for endemic diseases, probiotics, essential herbs, and the development of more disease-resistant populations.Keywords: health management, streptococcosis, Streptococcus agalactiae, tilapia